COVID-19 hasn't killed merchant acceptance of cash: Results from the 2023 Merchant Acceptance Survey - Angelika Welte; Katrina Talavera; Liang Wang; Joy Wu (Bank of Canada, 2024)
In recent years, the rise in digital payments has spurred a discussion in Canada and other countries about the future of cash at the point of sale. To better understand trends in payment methods accepted by Canadian businesses, including cash acceptance and the impact of innovations such as mobile payments, the Bank of Canada conducts the Merchant Acceptance Survey, a survey of small and mediumsized businesses. We find that 96% of these businesses in Canada accepted cash in 2023. Acceptance of debit and credit cards has increased since 2021 to 89%, and acceptance of digital payments has increased as well. However, the vast majority of merchants (92%) have no plansto go cashless in the future. Therefore, cash and digital payments continue to coexist at the point of sale, and Canada is far from being a cashless society.
Keywords: C8; D22; E4; L2; 330; Bank notes; Digital currencies and fintech; Econometric and statistical methods